Umstrittene Körperteile Eine Geschichte der Organspende in der Schweiz - Hofmann, Simon (Histoire, 2016)
How did the Swiss organ donation crisis come about? Despite reforms and advertising campaigns, from the late '80s, Swiss transplant medicine began to lament an increasing mistrust in organ donation and falling donor numbers. Simon Hofmann throws light on the role of doctors, nurses, family members and donees, but also of the media, politicians and the pharmaceutical industry. In doing so, he draws out the relations between hospital practices, public debates, and fictitious narratives about organ smuggling. He tells a complex and contradictory story of modern biomedicine at the edge of life and death, which is shaped as much by economic calculations as by utopian hope and traumatic fears.